The Centrality of Incarnation - Pederson, Ann Milliken (Zygon, 2008)
Abstract. What we urgently need at the beginning of the twenty-first century is a christological vision that can shape and inform a new and powerful way of helping humankind to interpret their place within the universe. A christological vision that is unintelligible and uninteresting can have a profoundly deleterious soteriological implication: the orbit of God's saving grace will not be wide enough to encompass the universal place of humankind. Arthur Peacocke's move is clear and to the point: Only when the foundations and universal scope of God's grace are fully established for all of creation, only then can the importance of God's specific work in Jesus the Christ be established.